IgG subclass distribution of autoantibodies in pediatric opsoclonus-myoclonus syndrome. - Beck, S; Fühlhuber, V; Krasenbrink, I; Tschernatsch, M; Kneifel, N; Kirsten, A; Jaeger, C; Kaps, M; Preissner, K; Lang, B; Rostasy, K; Blaes, F (2007)
Opsoclonus-myoclonus syndrome (OMS) in children is a rare disorder including a severe eye movement disturbance, myoclonia, ataxia and often developmental retardation. Both OMS forms, idiopathic or neuroblastoma-associated (paraneoplastic), have been suspected to be autoimmune. Recently, autoantibodies have been found in OMS sera. We here show that autoantibodies in OMS, both intracellular and surface binding, belong mainly to the IgG3 subclass, although the total serum IgG3 level is normal. These results support the autoimmune hypothesis and point to a protein autoantigen as antigenic target.